Low field RYDMR: effects of orthogonal static and oscillating magnetic fields on radical recombination reactions - Woodward, JR; Timmel, C; Hore, P; McLauchlan, K (2002)
Reactions involving spin correlated radical pairs as intermediates are known to be sensitive to applied static and/or oscillating magnetic fields. In the reaction yield detected magnetic resonance (RYDMR) technique, an electromagnetic field in resonance with the electron Zeeman splitting produced by a strong static field is used to perturb the singlet ↔ triplet interconversion of the radical pair and so to affect the yield of geminate recombination. New experiments are described in which weak radiofrequency fields (≲ 300 μT) in the frequency range 1-80 MHz are applied to radical ion pairs derived from pyrene and 1,3-dicyanobenzene, in the presence of a weak (≲ 3.0 mT) static magnetic field. Such experiments test the viability of RYDMR in low fields, provide insight into the crossover region between the zero-field and high field cases, and may give information on the distribution of radical pair lifetimes.